2013
DOI: 10.1002/evan.21355
|View full text |Cite
|
Sign up to set email alerts
|

Sociopolitical Complexity and the Bow and Arrow in the American Southwest

Abstract: The evolution of sociopolitical complexity, including heightened relations of cooperation and competition among large nonkin groups, has long been a central focus of anthropological research. Anthropologists suggest any number of variables that affect the waxing and waning of complexity and define the precise trajectories that groups take, including population density, subsistence strategies, warfare, the distribution of resources, and trade relationships. Changes in weaponry, here the introduction of the bow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The details of these cases are consistent with the most straightforward predictions of social coercion theory. Specifically, each reflects a high complexity ratio environment (high dependence on intensifiable maize cultivation) and displays the predicted strong archeological signal of increased complexity following local arrival of the bow.…”
Section: Comparative Tests Of Warfare and Social Coercion Theories: Tsupporting
confidence: 81%
See 2 more Smart Citations
“…The details of these cases are consistent with the most straightforward predictions of social coercion theory. Specifically, each reflects a high complexity ratio environment (high dependence on intensifiable maize cultivation) and displays the predicted strong archeological signal of increased complexity following local arrival of the bow.…”
Section: Comparative Tests Of Warfare and Social Coercion Theories: Tsupporting
confidence: 81%
“…Thus, the strong local capacity to generate front‐loaded storable resources is expected to maximize the enhancement of social complexity resulting from an increase in the scale of social cooperation. The massive field agriculture of the Ancestral Pueblo and Mississippians and large‐scale production of dried salmon in several localities apparently reflect examples of such production intensification.…”
Section: Intensifiable Resources Social Complexity and Coercion: Nementioning
confidence: 99%
See 1 more Smart Citation
“…There are various reasons not to favor foraging models for bow‐driven increases in social complexity. For example, many of the increases in social complexity in the North American Neolithic concern local agricultural revolutions, creating societies in which farming rather than hunting is the central food‐related adaptive strategy . New efficiency in hunting is an unlikely cause of such change.…”
Section: How Can the Bow Be A Cause Of Social Complexity Increase?mentioning
confidence: 99%
“…Hoffman (1997) is one of the researchers who have considered this variable, and he concluded that the prehistoric inhabitants of southern Arizona used projectile point blade margin treatment including serration to intentionally signal group affiliations. Hoffman (1997:95) recognized that the shaft and fletching were the most visible portions of arrows, and therefore these elements "were commonly decorated or designed to reflect individual ownership or tribal affiliation" (see also Mason, 1894:662;VanPool and O'Brien, 2013). He, however, focused on points because data from the shafts are not available.…”
Section: Introductionmentioning
confidence: 96%